2021
DOI: 10.3390/su13158349
|View full text |Cite
|
Sign up to set email alerts
|

Management of Green Intellectual Capital: Evidence-Based Literature Review and Future Directions

Abstract: This paper presents a systematic, evidence-based review of Green Intellectual Capital (GIC) management, a construct first introduced in 2008 and increasingly recognized as a management concept in recent years. This review covers the literature on GIC from 2008 to 2020 and addresses the role played by intellectual capital as a framework to promote sustainability in organizations. With the aim of clarifying our knowledge on the application of the GIC paradigm, this paper reviews the findings on the outcomes achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 83 publications
2
28
0
1
Order By: Relevance
“…Researchers have begun to pay increased attention to the management of GIC recently ( Benevene et al, 2021 ). Based on the definitions proposed by Chen (2008) , López-Gamero et al (2011) , and Chang and Chen (2012) , GIC refers to the sum of various intangible assets including knowledge, information, technology, and environmental protection and green management abilities, which create value and provide sustainable competitive advantages for enterprises.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Researchers have begun to pay increased attention to the management of GIC recently ( Benevene et al, 2021 ). Based on the definitions proposed by Chen (2008) , López-Gamero et al (2011) , and Chang and Chen (2012) , GIC refers to the sum of various intangible assets including knowledge, information, technology, and environmental protection and green management abilities, which create value and provide sustainable competitive advantages for enterprises.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Relational capital contributes to promoting sustainability programs in an effort to build organizational relationships with external stakeholders. Relational capital also plays a role in positioning social and environmental programs to increase the reputation and value of the organization Meanwhile, structural capital helps provide the infrastructure for sustainability programs to increase the organization's competitiveness and market share (Alvino et al, 2021;Benevene, Buonomo, Kong, Pansini, & Farnese, 2021). Several studies have shown that IC encourages SMEs toward more sustainable performance, aligning with the Sustainable Development Goals (SDGs) (Ahmad et al, 2022;Alvino et al, 2021;Khan et al, 2021;Yusliza et al, 2020).…”
Section: Intellectual Capital and Sustainability Performancementioning
confidence: 99%
“…Meanwhile, relational capital helps build good organizational relationships with external stakeholders. Thus, IC becomes a strategic internal organizational resource to achieve a competitive advantage (Dar & Mishra, 2020) as well as increased competitiveness and financial growth (Benevene et al, 2021;Gross-Gołacka et al, 2020). Even though IC has become a rare, valuable, and irreplaceable organizational asset (Benevene et al, 2021), firms are more likely to gain a competitive advantage by investing in intangible assets (Gross-Gołacka et al, 2020;Sapta., Rustiarini, Kusuma, & Astakoni, 2021).…”
Section: Intellectual Capital and Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The research on the topic of intellectual capital in the modern sense and conditions is largely limited by the difficulty of its measuring and evaluating [13,14]. At the same time, many scientific studies mainly bind intellectual capital with intangible assets and the implementation of innovative potential [15,16]. However, this concept is very multifaceted, and empirical research needs to be studied for assessing the role of ICs in companies' performance.…”
Section: Literature Reviewmentioning
confidence: 99%